TRANSFORMATIONAL LEADERSHIP INFLUENCE ON SELF-EFFICACY OF LECTURERS OF HIGHER INSTITUTIONS IN KATSINA STATE NIGERIA - Abba Yangaiya Salisu; Binta Ado Ali; Umar Mamman (International Humanities and Applied Science Journal, 2022)
Abstract- The study examines the influence of transformational leadership on self-efficacy of lecturers of higher institutions in Katsina state Nigeria. Data was collected from 403 lecturers in higher institutions in Katsina state.  Statistical Package for Social Science Research (SPSS) version 20.0 was used to analyze the data collected. Results depict that transformational leadership influences lecturer’s self-efficacy in higher institutions used in the study (R2 .53). The study brings to the fore the need for stake holders in  higher institutions to as much as possible practice transformational leadership in order to enhance self-efficacy among lecturers in their respective institutions. The study adds to few studies conducted on transformational leadership and self-efficacy in Nigeria in general and Katsina state in particular.